Strategi Dinas Pariwisata dalam Pengembangan Infrastruktur Objek Wisata Telaga Ngebel di Kabupaten Ponorogo - Galuh Istu Sripambudi; Yusuf Adam Hilman; Bambang Triono (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
The development of tourism is the responsibility of the ngebel lake owned by the Ponorogo Regency, which means the department of tourism and the department of public. The development of carried out so far constituted by a strategy and planning involves various parties with a painful consideration, so that important to know how that infrastructure development practices. This study's aim is to see how the process of implementation of the infrastructure development in the Lake of ngebel tourist attractions. This research using the kind of research qualitative descriptive, with the data through the interviews and documentation. Research describes a development strategy undertaken by departments tourism agency and the department of public proven to have to reap the harvest through the output of reform in the infrastructure sector. And facilities are also facilities to improve the quality of supporting the development of tourism objects. Ngebel Lake, So the example is he's made a gazebo, identity monument, identity statue of (Baru Klinting), and prowling water recreation in the form of a duck boat and speedboat. In carrying out construction in a Telaga Ngebel's tourist attraction, Dinas Pariwisata and Dinas Pekerjaan Umum always attention to two aspects of strategy and contributing factors of infrastructure development. The goal is to increase the appeal and sale value for sustainability the prospect of vacation of Telaga Ngebel in the future. By the interviews that have been don in this resort, the author can at least find a conclusion or ideas for strategic infrastructure development in Telaga Ngebel's tourist attractions. That there are still some constraints and financial problems that keep us from the maximum realizing development of infrastructure.